Customer Relationship Management as a Firm-level Factor and its role in Firm Performance: A Study on the Firms Listed at Nairobi Securities Exchange - Ndungu Machiri, Samuel; Oloko, Margaret; Karanja Ngugi, John; Odhiambo, Romanus (Journal of Information Systems and Technology Research, 2024)
The study sought to examine the relationship between customer relationship management and performance of firms listed at Nairobi Securities Exchange. While the listed firms remain integral in the country’s economy, their continued performance has been declining over the years. This has seen some of the firms get delisted and others suspended from trading due to subsequent years of loss-making. Customer relationship management on the other hand has been found to be instrumental in determining the performance of modern firms, in the midst of growing competition and dynamic operating environment. The motivation of this study was therefore the limited literature on the relationship between customer relationship management and performance of listed firms. The study utilized a descriptive-exploratory research design, where 240 senior management personnel drawn from the 64 listed firms were surveyed using a structured questionnaire. The data was analysed using SPSS and Amos software for descriptive statistics, regression model and structural equation modelling respectively. The findings revealed that customer relationship management had a significant influence on the performance of firms listed at the NSE (R2 = .265; β = 0.353; P=0.0001<0.05). It was therefore concluded that customer relationship management as a frim-level factor is instrumental in determining the performance of the listed firms at the NSE. The study recommended the need for the management of the listed firms to be at the forefront of pushing for enhanced customer relationship management so as to strengthen the firms performance.